Analisis Kesulitan Belajar Siswa Broken Home melalui AUM PTSDL di SMP PAB 8 Sampali - Wiweka Rajagukguk; Miswanto Miswanto; Rosalinda Pardede; Nazwa Elminda Mendrof; Tary Azahra; Desi Sri Rezeki Boangmanalu (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
AUM PTSDL is a problem expression tool in a typical student to see the effectiveness of student learning. The purpose of this research is to provide an overview of the implementation of the AUM PTSDL problem directly to students, especially in PAB 8 sampali junior high school students. in the application of AUM PTSDL can accelerate overcoming problems in learning, especially broken home students. This research uses a descriptive method with a case study approach. This research was conducted at PAB 8 Sampali Junior High School on October 23-5, 2020. The subjects in this study were 9th grade AUM PTSDL students at SMP PAB 8 sampali. Based on the results of the research, the implementation of AUM PTSDL at SMP PAB 8 sampali has been carried out and shows that students have broken home problems that students are carried out AUM with several problems, namely, PTSDL. The conclusion is that students who have problems in AUM PTSDL will provide benefits in the form of support or advice to improve the quality of student learning from counseling teachers in schools.